Empirical Analysis of Farmers' Intention to Adopt Sustainable Agricultural Practices. (March 2019) - Syan, Amanjot Singh; Kumar, Vikas; Sandhu, Vikram; Hundal, Bikramjit Singh
The present research aims to study the farmers' intention to adopt sustainable agriculture practices. The sample size of 283 respondents has been considered and responses have been recorded from different areas of Punjab state (India) using a research schedule. The study considered six dimensions namely perceived usefulness; self efficacy; extension services; social capital; facilitating conditions and compatibility have been taken from the existing literature. The data thus collected, has been analysed using exploratory factor analysis, confirmatory factor analysis, and multiple regression analysis. The results of the study confirmed that perceived usefulness, self efficacy and extension services play a significant role whereas social capital, facilitating conditions, and compatibility have no significant impact on the decisions to implement sustainable Agricultural practices.